Development of Folate-Functionalized PEGylated Zein Nanoparticles for Ligand-Directed Delivery of Paclitaxel - Zar Chi Soe; Wenquan Ou; Milan Gautam; Kishwor Poudel; Bo Kyun Kim; Le Minh Pham; Cao Dai Phung; Jee-Heon Jeong; Sung Giu Jin; Han-Gon Choi; Sae Kwang Ku; Chul Soon Yong; et al. (MDPI AG, 2019)
In this study, we investigated the active targeted delivery of a hydrophobic drug, paclitaxel (PTX), via receptor-mediated endocytosis by folate receptors expressed on cancer cells using a protein-based nanoparticle system. PTX was loaded on zein nanoparticles and conjugated with folate (PTX/Zein-FA) to estimate its chemotherapeutic efficacy in folate receptor-expressing KB cancer cells. PTX/Zein-FA nanoparticles were successfully developed, with a nanoparticle size of ~180 nm and narrow polydispersity index (~0.22). Accelerated release of PTX in an acidic environment was observed for PTX/Zein-FA. An in vitro cellular study of PTX/Zein-FAs in KB cells suggested that PTX/Zein-FA improved the cytotoxic activity of PTX on folate receptors overexpressed in cancer cells by inducing proapoptotic proteins and inhibiting anti-apoptotic proteins. In addition, PTX/Zein-FA exhibited anti-migratory properties and could alter the cell cycle profile of KB cells. A549 cells, which are folate receptor-negative cancer cells, showed no significant enhancement in the in vitro cellular activities of PTX/Zein-FA. We describe the antitumor efficacy of PTX/Zein-FA in KB tumor-bearing mice with minimum toxicity in healthy organs, and the results were confirmed in comparison with free drug and non-targeted nanoparticles.